The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1993
DOI: 10.1002/pca.2800040604
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of bilobalide and ginkgolides A, B, C and J by means of nuclear magnetic resonance spectroscopy

Abstract: A quantitative 'H NMR procedure for the determination of bilobalide and ginkgolides A, B, C and J in Ginkgo bilobu leaves and in phytopharmaceuticals without prior chromatographic separation of the mixture has been developed. The method is based on the comparison of the integral of each H-12 proton of the five ginkgo terpene trilactones with that of the olefinic protons of the internal standard (maleic acid). These protons are all well separated at 200 MHz and occur in a less crowded region of the NMR spectrum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 17 publications
0
38
0
1
Order By: Relevance
“…Based on earlier 1 H NMR investigations of Ginkgo biloba extracts (van Beek et al 1993; Choi et al 2003; Li et al 2004), spectra of all samples were acquired in acetone- d 6 with an inter-pulse delay of 2.84 s, which assured full relaxation of magnetization between excitations. The spectra constitute the dataset for the multivariate data analysis, and an overview of the spectra is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Based on earlier 1 H NMR investigations of Ginkgo biloba extracts (van Beek et al 1993; Choi et al 2003; Li et al 2004), spectra of all samples were acquired in acetone- d 6 with an inter-pulse delay of 2.84 s, which assured full relaxation of magnetization between excitations. The spectra constitute the dataset for the multivariate data analysis, and an overview of the spectra is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…10 -12 Moreover, totally different approaches, such as biological standardization using the PAF-antagonist properties of ginkgolides 13 and 1 H NMR spectroscopy, 14 have been proposed. Recently, Camponovo et al 15 developed an HPLC method using either thermospray (TSP) MS detection or evaporative light scattering detection (ELSD).…”
Section: Introductionmentioning
confidence: 99%
“…To standardize commercial ginkgo products and to carry out quality control studies, assays have been reported based on a wide variety of analytical techniques including HPLC or capillary electrophoresis with UV absorbance detection [20,21], HPLC with refractive index detection [22], HPLC with evaporative light scattering detection (ELSD) [23], gas chromatography (GC) with flame ionization detection [24], GC-mass spectrometry (GC-MS) [25], NMR [26], and liquid chromatography-mass spectrometry (LC-MS) [27][28][29][30]. Although ginkgo extracts usually contain considerable quantities of flavonoids which have strong UV absorption, terpenoid lactones lack UV chromophores so that even trace amounts of co-eluting compounds such as the abundant flavonoids might interfere with their detection.…”
Section: Introductionmentioning
confidence: 99%